PENGARUH KATALOG PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA BENGKEL LAS CITRA PERSADA JOMBANG TANGERANG SELATAN - Adbilah, Rizal; Supiandi, Gojali (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the Product Catalog Variable (X1), Price (X2), Purchasing Decision (Y), and the Influence of Product Catalog and Price on Purchasing Decisions at the Citra Persada Jombang Tangerang Selatan Welding Workshop. This research method uses a quantitative method with a quantitative descriptive approach and the population in this study is 154 consumers. The sample used in this study uses the entire population of 99 consumers as respondents. In this study the sampling technique used is probability sampling. The results of the Product Catalog variable have a significant effect on Purchasing Decisions with a t-count of 10.267> t-table of 1.984 and a Sig. value <0.05 (0.0000 <0.05). The results of the Price variable have a significant effect on Purchasing Decisions with a t-count of 14.855> t-table of 1.984 and a Sig. value <0.05 (0.0000 <0.05). The results showed that the Product Catalog and Price variables simultaneously significantly influenced Purchasing Decisions, with an f-value of 120.617 > 3.092 and a Sig. value of <0.05 (0.000 < 0.05).